Impact of monetary and financial policies on the performance of commercial banks in Iraq - BBAC banks and Kurdistan International bank - Karem, Langa Esmael; Bayz, Hakar Abubakir; Darwesh, Mahabad Ghafur; Ali , Diary Jalal (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The research aims to clarify the impact of both monetary and fiscal policy on the performance indicators of commercial banks. The study uses multi-stage linear regression method for data analysis for a sample of BBAC bank and KIB in Iraq for the period 2006-2019. The results show that the monetary policy indicators of money supply and inflation have had significant impact on the profitability solvency indicators of BBAC bank. The money supply index had an impact on the profitability index of KIB. However, fiscal policy has no impact on the selected banking performance indicators. Furthermore, the results show that the fiscal policy indicators of revenues, expenditures and the general budget had no impact on the performance indicators of the sample banks. Monetary policy indicators of tight money supply, exchange rate and inflation have had mixed impact on the banks performance indicators. The results of the quantitative analysis show that monetary and financial policies do not have a similar impact on the performance of BBAC and KIB for the period 2006-2019. As recommendation, the monetary authority should seek maintain the growth rates of the money supply consistent with economic activity. The monetary authority needs to reduce inflation rates and keep it low as a monetary policy objective in Iraq.